Acoustic characteristics of healthy voices of adults: From young to middle age - Spazzapan, Evelyn Alves [UNESP] (2018)
Purpose: Characterize voices of adult individuals without vocal complaints and verify the effect of gender and age with the use of acoustic measures. Methods: One-hundred and seventy-six voice recordings belonging to adults between 19 and 59 years old, divided into four age groups, for decade, recorded in a database were analyzed. All voices analyzed were classified with no deviation in vocal quality. Acoustic analysis of the parameters was performed: Fundamental Frequency (sustained vowel and connected speech), Jitter, Shimmer and Noise-to-Harmonic Ratio through Multi Dimension Voice Program (KayPentax) software. The effect of gender, age and possible interactions were verified through the Factorial Anova test. When necessary, post hoc was performed with the Least Significant Difference test. Results: There were changes in the voice as a function of age, with a decrease in the Fundamental Frequency in the vowel and connected speech modalities in women and in the Fundamental Frequency of the speech in men. In men, an increase in shimmer measure was observed with the advancing age. Differences between genders were found in the measures of Fundamental Frequency, Jitter and Noise to Harmonic Ratio. Conclusion: Vocal changes due to advancing age can be identified acoustically at the end of adulthood, and in women, these changes can be marked previously to the menopausal period.